ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KONDISI RUMAH SEHAT DI DESA BANDUR PICAK KECAMATAN KOTO KAMPAR HULU TAHUN 2017 - ade dita puteri (Universitas Pahlawan, 2017)
Environmental-based diseases contribute more than 80% of diseases suffered by infants and toddlers. This situation indicates that there is still a low coverage and quality of environmental health interventions. Based on Indonesia's Health Profile in 2014, it was found that achieving healthy homes in Indonesia was 61.81%. While the national target is set at 80% (Ministry of Health, 2014). The research objective was to determine the factors related to healthy home conditions in Bandur Picak Village, Koto Kampar Hulu Subdistrict in 2017. The cross-sectional study design was carried out on July 24-30 2017 in Bandur Picak Village, Koto Kampar Hulu Sub-District. The population in this study was 250 houses. The sample in this study was 95 houses. The sample technique used was simple random sampling with the instrument used in the form of a questionnaire. The data obtained were analyzed by the chi square test. The results showed that there was a relationship between education and healthy home conditions p value = 0.000, indicating that there was a relationship between knowledge with healthy home conditions p value = 0.017, indicating a relationship between attitudes and healthy home conditions p value = 0.000. It is expected that the Koto Kampar Hulu health center will increase public knowledge about the condition of a healthy home by providing information and information about the condition of a healthy home.